Exploring the Relationship Between Serum Magnesium, Inflammation, and Chronic Pain in a Vermont Primary Care Population. (29th May 2020) - Littenberg, Benjamin; Ahern, Thomas; Tarleton, Emily
Abstract: Objectives: We sought to describe the relationship between serum magnesium, inflammation, and chronic pain in adult primary care patient. Methods: We sought to describe this relationship utilizing a cross-sectional analysis of medical records from 5639 adults (mean age 59 years; 42% men) seen in The University of Vermont Medical Center primary care clinics between 2015 and 2018. Patients with at least one serum magnesium level, C-reactive protein (CRP, a measure of inflammation) level, and chronic pain score (self-reported visual analogue scale) were included. Results: Univariate analysis confirmed the relationship between serum magnesium and chronic pain (−0.31 points/mg/dL; 95% CI −0.47, −0.14; P < 0.001). However, when serum magnesium and CRP were both included in the model, the relationship with pain is unclear (N = 1345; CI −0.003, 0.002; P = 0.69). Conclusions: For adults seen in primary care, lower serum magnesium levels are associated with chronic pain. This inverse relationship is not explained by random noise, including age and gender. The complex relationship between serum magnesium, CRP, and pain is complex requires further exploration. Funding Sources: None.